Syndemics of coronaviurs disease and aging: the interplay among nutrition, the immune system and health outcomes - Iqbal, Sehar; Ali, Inayat (International Journal of Public Health Science (IJPHS), 2025)
The coronavirus disease 2019 (COVID-19) pandemic revealed “many pandemics”. Right from the beginning of the COVID pandemic and various intimidating waves of new variants seriously affected vulnerable populations, including the elderly. This scoping review aimed to summarize the available data on nutrition and immune response during aging and associations between the immune system and viral infections in the older population. The review particularly emphasizes micronutrients including vitamins C, D, zinc, and selenium and their relations to COVID-19 infection. We have summarized the available literature related to the nutritional management of COVID-19 infection to reduce adverse disease outcomes. The review found that the coexistence of micronutrient deficiencies, immune dysfunction, and high infection exposure increases the risk of mortality in older people with COVID-19. Most studies confirmed a positive association between vitamin D status or supplementation and its effect on COVID-19, whereas a few other studies reported a low zinc and selenium status in COVID-19 infected people. Immediate and adequate nutritional management could help tackle the adverse health consequences in elderly. Hence, the pandemic like this requires a comprehensive approach to understand all related aspects and needs further in-depth investigations related to micronutrient supplements to enhance immunity in COVID-19 infected older population.